Problematika razvoja mest in spreminjanja rabe mestnega prostora - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Rapid growth of cities causes signi. cant changes in the use of their space. Besides basic economic development factors, the principal development factors are technology, demographic trends, policy, social structure, culture and globalisation. City is becoming an increasingly heterogeneous space. Basically, this is indicated by rapid increase in the demand for construction permits and for information as regards the activities, which affect the environment, as well as by a number of problems arising in association with the planned use and investitors' desires.
Keywords: mesta; urbani razvoj; mestni prostor; raba prostora; raba tal; spremembe; Ljubljana